CUSTOMERS' ATTITUDES AND PURCHASE INTENTIONS FOR LUXURY GOODS: AN EXAMINATION OF ONLINE SHOPPING OF JADE CARVING PENDANTS DURING THE COVID-19 PANDEMIC IN MALAYSIA - Zhengping Zhang; Tanawat Teepapal (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The research has depicted the image of the influencing factor of purchasing behavior of consumers of luxury products. The purchasing behavior of customers of luxury brands relies on market trends. Due to this, businesses need to understand and analyze the movements of the market, including the demand of consumers in the post-pandemic situation, to improve their market position and build healthy relationships with consumers. The study brings out the aspects of purchasing of Jade carving pendant that get broader assimilation of data facts on a significant basis. Indefinite primary quantitative data sets that are descriptive have been incurred to formulate the significance of the research study. The collected data from the survey participants are effectively analyzed with the help of the SPSS software and descriptive statistical analysis. The analysis of the study has been divided into two parts, namely multivariate analysis and data quality analysis. The reliability and validity assessments have been done based on the data collected from the questionnaire. Conclusions and suggestions have been provided for the current study. The suggestions of the study are based on the improvement of online marketing of the luxury brand “Jade Carving Pendants” and, at the same time, future suggestions for enhancing research with relatable topics. The current study has successfully drawn practical conclusions and, at the same time, improved the online marketing and consumer perspectives and experience of luxury brands.